Criminal Law Significance of Final Procedural Decisions on Exemption from Criminal Liability and Punishment - K. N. Karpov (Сибирское юридическое обозрение, 2024)
The subject of the study is the provisions of criminal, criminal procedural and criminal exe cutive legislation, as well as acts of interpretation and judicial practice related to the legal regulation of exemption from criminal liability or punishment of those who have committed a crime. The purpose of the study is to compare the provisions of the criminal law regulating the grounds for exemption from criminal liability and punishment with the norms of criminal procedure law regul ating the procedure for making final decisions on the termination of a criminal case (prosecution). Using the general scientific dialectical method, as well as the methods of formal legal analysis and synthesis, the author identified and demonstrated contradictions between the norms of substantive and procedural law in terms of substantiating the grounds for terminating a criminal case (prosec ution) and the grounds for exemption from criminal liability (punishment). Conclusions. Ignoring the provisions of the Criminal Code of the Russian Federation, which contains an exhaustive list of grounds and conditions for exemption from criminal liability and punishment, results in uncertain legal consequences for those who have committed crimes, both as to criminal law coercive measures and determining the general legal consequences for a person committing a crime. Thus, in some cases, courts are forced to make decisions on exemption from punishment due to the expiry of the statute of limitations, despite the fact that Art. 78 of the Criminal Code of the Russian Federation requires that such persons be exempted from criminal liability. On the other hand, Art. 398 of the Code of Criminal Procedure of the Russian Federation contains a special provision for deferring the execution of a sentence, which is not found in the Criminal Code of the Russian Federation either as a basis for exemption from liability or from punishment. It is proposed to eliminate the exis ting contradictions in the branches of law by unifying the norms of criminal procedural legisl ation and bringing them into conformity with the norms of substantive criminal law that regulate the e xemption from criminal liability and punishment.